Building up PtII−Thiosemicarbazone−Lysine−sC18 Conjugates - Haseloer, Alexander; Lützenburg, Tamara; Strache, Joss Pepe; Neudörfl, Jörg; Neundorf, Ines; Klein, Axel (Chembiochem : a European journal of chemical biology, 2021)
Three chiral tridentate N^N^S coordinating pyridine‐carbaldehyde (S)‐N4‐(α‐methylbenzyl)thiosemicarbazones (HTSCmB) were synthesised along with lysine‐modified derivatives. One of them was selected and covalently conjugated to the cell‐penetrating peptide sC18 by solid‐phase peptide synthesis. The HTSCmB model ligands, the HTSCLp derivatives and the peptide conjugate rapidly and quantitatively form very stable PtII chlorido complexes [Pt(TSC)Cl] when treated with K2PtCl4 in solution. The Pt(CN) derivatives were obtained from one TSCmB model complex and the peptide conjugate complex through Cl−→CN− exchange. Ligands and complexes were characterised by NMR, IR spectroscopy, HR‐ESI‐MS and single‐crystal XRD. Intriguingly, no decrease in cell viability was observed when testing the biological activity of the lysine‐tagged HdpyTSCLp, its sC18 conjugate HdpyTSCL‐sC18 or the PtCl and Pt(CN) conjugate complexes in three different cell lines. Thus, given the facile and effective preparation of such Pt‐TSC‐peptide conjugates, these systems might pave the way for future use in late‐stage labelling with Pt radionuclides and application in nuclear medicine. Late‐stage labelling: Chiral pyridine‐carbaldehyde (S)‐N4‐(α‐methylbenzyl)thiosemicarbazones were lysine modified (TSCLp) and covalently conjugated to the cell‐penetrating peptide sC18 by SPPS. Very stable PtII complexes [Pt(TSC)X] (X=Cl or CN) were synthesised, and the biological activity of the TSCLp, conjugate TSCL‐sC18, or Pt conjugate complexes was studied.